Student Perspective on Technology Enabled/Enhanced Active Learning in Educational: Rasch Measurement Model - Hassan, Nur Farha; Puteh, Saifullizam; Sanusi, Amanina Muhamad; Zahid, Nor Hartini Che Mohamad (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Nowadays, the industrial revolution 4.0 had given a great impact on education. An active environment which applied technology in education can developed multiple skills in students. Technology Enabled/Enhanced Active Learning (TEAL) is one of the active environments that used technology in education. TEAL is the combination of several active learning domains which enhances students' understanding of learning and built job-related skills. However, students have lack of knowledge in their field which led to increase in unemployment of students. Hence, TEAL can help students in perform their practical works to develop knowledge and skills in students. This pilot study was distributed survey question about create an active and effective environment using TEAL application among the engineering students. The survey is consisted of 141 items and was distributed to 40 respondents. This pilot study used Rasch Measurement Model for measuring the validity and reliability of survey questions. Winsteps software is used to check the functionality of the item in terms of (i) Reliability and separation of respondents - items; (ii) detect the polarity items of PTMEA CORR Value; (iii) the item fit based on MNSQ Value; and (iv) Determine the dependent items based on the standardized residual value measurement correlation. The final result 109 items is suitable to use for measurement of the real study in future work.